2019
DOI: 10.1177/0731948718823080
|View full text |Cite
|
Sign up to set email alerts
|

Schema-Based Instruction for Mathematical Word Problem Solving: An Evidence-Based Review for Students With Learning Disabilities

Abstract: The purpose of this review is to determine the evidence base classification of schema-based instruction (SBI) as an intervention to improve word problem-solving outcomes in mathematics for students with learning or mathematics disabilities in Grades K–12. Using the Council for Exceptional Children’s quality indicators (QIs) and standards, we reviewed both single-case and group design studies to classify the evidence of SBI. Results of this review indicate that SBI is a potentially evidence-based practice (EBP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 46 publications
(110 reference statements)
3
49
0
3
Order By: Relevance
“…In Jitendra et al’s (2015) review, none of the single-case studies published before 2012 met Horner et al’s (2005) quality indicators. Cook, Collins, Morin, and Riccomini (2019) identified SBI as a promising EBP for students with a specific learning disability (SLD). Despite five single-case and one quasi-experimental design meeting quality indicators, an insufficient number of students with an SLD were included.…”
Section: Schema-based Instruction (Sbi)mentioning
confidence: 99%
See 1 more Smart Citation
“…In Jitendra et al’s (2015) review, none of the single-case studies published before 2012 met Horner et al’s (2005) quality indicators. Cook, Collins, Morin, and Riccomini (2019) identified SBI as a promising EBP for students with a specific learning disability (SLD). Despite five single-case and one quasi-experimental design meeting quality indicators, an insufficient number of students with an SLD were included.…”
Section: Schema-based Instruction (Sbi)mentioning
confidence: 99%
“…To date, four systematic reviews and meta-analyses investigated the effectiveness of schema instruction on the mathematical problem solving of students (Cook et al, 2019; Peltier & Vannest, 2017; Peltier, Vannest, & Marbach, 2018; Powell, 2011). Several themes emerged.…”
Section: Schema-based Instruction (Sbi)mentioning
confidence: 99%
“…Even within the limited transcripts in this current study, both once-off and continuous misunderstandings and misapplications are observed. Unfortunately, the literature most often frames these through a lack of prior knowledge [1,2,4,6,17].…”
Section: On the Area Formula Of A Rectanglementioning
confidence: 99%
“…Due to the need to help students with LD learn to solve WPs efficiently and effectively, research in special education has led to the development of interventions focused on improving WP outcomes. Thus, over the last three decades, researchers have examined the effectiveness of WP instruction for students with LD and mathematics difficulties (Cook et al, 2020;Hwang & Riccomini, 2016;Jitendra et al, 2015Jitendra et al, , 2016Jitendra et al, , 2018Jitendra & Xin, 1997;Montague & Dietz, 2009;Peltier et al, 2018;Powell, 2011;Xin & Jitendra, 1999;Zheng et al, 2013). These studies compared the effects of WP instruction by student characteristics such as disability status (e.g., LD and mathematics difficulties) or grade (e.g., elementary, secondary, and postsecondary) and intervention features such as interventionist (e.g., researcher, teacher, and both), WP tasks (e.g., arithmetic or fractions, ratio and proportion, META-ANALYSIS OF WORD-PROBLEM INSTRUCTION 7 and algebra), and instructional components (e.g., use of visuals, manipulatives, technology, and strategy).…”
Section: Previous Syntheses and Meta-analyses Of Wp Instructionmentioning
confidence: 99%
“…In general, students with LD and mathematics difficulties demonstrated improved performance on WP tasks after receiving WP instruction, and the weighted average effect sizes showed significant improvements. Many researchers (Cook et al, 2020;Hwang & Riccomini, 2016;Jitendra & Xin, 1997;Jitendra et al, 2015;Powell, 2011;Zheng et al, 2013) identified positive effects from use of explicit and systematic instruction, in terms of modeling, guided practice, monitoring, corrective feedback, or independent practice. Other researchers (e.g., Cook et al, 2019;Jitendra et al, 2015Jitendra et al, , 2016Jitendra et al, , 2018Peltier et al, 2018;Powell, 2011;Xin & Jitendra, 1999) determined a high degree of effectiveness when incorporating representational techniques, including the use of schematic diagraming with the identification of WP structures.…”
Section: Previous Syntheses and Meta-analyses Of Wp Instructionmentioning
confidence: 99%